PENDAMPINGAN PENYUSUNAN RENCANA PEMBERDAYAAN KOLABORATIF ANAK JALANAN DI YAYASAN INTAN MAHARANI PALEMBANG: PENDAMPINGAN PENYUSUNAN RENCANA PEMBERDAYAAN KOLABORATIF ANAK JALANAN DI YAYASAN INTAN MAHARANI PALEMBANG - Syahri, Syahri; Adiah, Masayu; Nur Intan, Lies; Herdayani, Fitri; Junita, Rita; Supardi, Supardi (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2026)
Street children are one of the problems in urban areas, including in the city of Palembang. The number of street children is increasing from time to time, so comprehensive and sustainable efforts are needed to resolve the problem. To make these efforts, the involvement of many parties is required, one of the parties that plays an important role is civil society organizations, namely non-governmental organizations. The Intan Maharani Foundation is one of the Civil Society Organizations that has a serious concern for fostering street children in the city of Palembang. To help improve their role, this community service activity was carried out, namely, strengthening the collaborative fostering of street children. The activity was carried out using the brainstorming and discussion method. The leaders and staff of the foundation understand the importance of collaboration with stakeholders, conducting analysis of support and resources, and designing follow-up plans for cooperation. From the results of the workshop, the Intan Maharani Foundation can build a wider stakeholder network so that it will increase its role in urban poverty issues, including street children. Keywords: street children, collaborative, coaching, stakeholders